Prevalence of potentially inappropriate medications and prescription dynamics in elderly hospitalized patients in Spain - T. Puig; L. Leache; N. M. González-Senac; E. Carreras; M. Gutiérrez-Valencia; L. Losa; J. L. Revuelta-Herrero; P. Marrero-Álvarez; M. de Miguel; A. Aguirrezabal Arredondo; A. Aranguren; A. Vilariño; et al. (BMC Geriatrics, 2024)
Abstract Purpose In recent years, the need for a more appropriate prescription of medications in the older population has emerged as a significant public health concern. In this study, we aimed to evaluate the prevalence of potentially inappropriate medications (PIM) in hospitalized adults aged ≥ 75. Patients and methods This was a retrospective descriptive observational study of patients at 16 hospitals in Spain. The study population included inpatients aged ≥ 75 admitted during a 7-day period (May 10 to 16, 2021). Data were obtained from the pharmacy databases of the participating hospitals. The list of PIMs was based on the Beers, STOPP-START, EU-PIM and PRISCUS criteria. Results A total of 4,183 patients were included. PIMs were detected in 23.5% (N = 1,126) of the cohort. The prevalence rates at the participating hospitals ranged from 10% to 42.5%. The PIM/patient ratio was 1.2. The most common PIMs were midazolam, dexketoprofen, diazepam, and doxazosin, all of which (except for doxazosin) were more common in women. Benzodiazepines accounted for 70% of all PIMs. In 35% of cases, the PIMs were initiated before hospital admission. Of the 818 PIMs initiated during hospitalization, the two most common were benzodiazepines (49%) and anti-inflammatory drugs (25%). At discharge, only 4.9% of the PIMs initiated during the hospital stay were still prescribed. Conclusion In this population of older hospitalized patients, the overall prevalence of PIMs was moderate. However, the prevalence rate at the participating hospitals was highly variable. In most cases, PIMs prescribed prior to hospitalization for chronic conditions were not withdrawn during the hospital stay. No significant increase in PIMs was observed from pre-admission to post-discharge. These findings underscore the need for multidisciplinary interventions to optimize the pharmaceutical treatment in older adults in the hospital setting to reduce the consequences of PIMs in patients.